Critique of the Spirit. Issue 1 (27th July 2022) - Christopher, Stephen
Abstract : The problem of tribal casteism – of Indian Scheduled Castes (SC) partially integrated into Scheduled Tribes (ST), facing discrimination without constitutional protections as doubly subaltern – is nearly absent in scholarship. The Halis of Kangra district, in the mountainous state of Himachal Pradesh, are one such SC community. Although most identify as Gaddi, the local tribe receiving coveted ST benefits, they are politically misrecognized. Through house church ethnography, this article explores how Hali sociopolitical liminality as tribal Dalits informs their popular Protestantism. By closely attending to vernacular hermeneutics, the sociopolitical context that shapes Hali textual ideologies, and homiletic emphases on protection from malign Gaddi spirits, I argue that Hali Protestants practise transgressive resignifications. The vocational roots of Hali symbolic pollution (ploughing and exorcism) are proudly reclaimed; Gaddi pastoralism, a contested terrain of caste exclusion, is reimagined as privileging Halis; Christ as the 'Giver of Help' is invoked as freedom from Gaddi spiritual affliction. These interpretive practices parallel broader efforts to realign discursive and social power within the Gaddi tribe.